Photography and its violations - Roberts, John, 1955- (Columbia themes in philosophy, social criticism, and the arts., 2014)
Theorists critique photography for "objectifying" its subjects and manipulating appearance for the sake of art. In this bold counterargument, John Roberts recasts photography's violating powers and aesthetic technique as part of a complex "social ontology" that exposes the hierarchies, divisions, and exclusions behind appearances. Photography must "arrive unannounced" and "get in the way of the world," Roberts argues, committing to the truth-claims of the spectator over the self-interests and sensitivities of the subject